Spectrum and Antibiotic Resistance Pattern of Bacteria Causing Urinary Tract Infections (UTI) in a Tertiary Care Hospital (Journal of Surgical Sciences, 2020)
Background: Urinary tract infection (UTI) is one of the most common bacterial infections encountered by clinicians particularly in developing countries. Current knowledge on antimicrobial resistance pattern is essential for appropriate therapy. The aim of the present study was to identify the causative organisms for UTI and to determine the antibiotic susceptibility pattern of organisms causing UTI.Method: This cross sectional study was carried out in the department of Microbiology, Sir Salimullah Medical College, Dhaka, from a period of January 2014 to December 2014.Results: Out of 2136 clinical sample of urine, 430 (20.1%) showed significant bacterial growth. Escherichia coli was the commonest urinary pathogen (76.3%), followed by Pseudomonas spp. (7.9%), Proteus spp. (7.2%), Klebsiella spp., Citrobacter spp. (1.9% each) and Staphylococcus aureus (1.6%). Isolated uropathogens showed highest resistance for Amoxycillin (86%-97%) and Cefradin (71%-100%), resistance rate for other commonly used antimicrobial agents was high; Cefixime (52%-85%), Ceftriaxone (50%-71%), Ciprofloxacin (50%-88%), Cotrimoxazole (50%-75%), Gentamicin (57%-75%) and Nitrofurantoin (43%-100%), while uropathogens were least resistant to Imipenem (0%-15%) and Amikacin (0%-29%).Conclusion: Due to high degree of resistance to commonly used antimicrobials to treat UTI, routine monitoring and evaluation studies should be conducted to update physicians’ knowledge about most effective antibiotics for treatment of UTI.Journal of Surgical Sciences (2019) Vol. 23 (1) : 13-18